2008
DOI: 10.3846/1648-4142.2008.23.273-278
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Urban Traffic Based Noise Pollution in the City of Kirikkale, Turkey

Abstract: The study presents an investigation into traffic based noise pollution in the city of Kirikkale, Turkey. For this purpose, traffic noise levels were measured at 15 intersections across the city during three peak times ‐ morning (08:00–09:00), noon (12:30–13:30) and evening (17:00–18:00) hours. The comparison of Leq values against the limit values of the Turkish Noise and Control Regulations for Settlement Zones showed that Leqvalues exceeded the limits at all stations. A linear regression analysis performed be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…Deformations limit driving properties such as vehicle control, driving comfort and also cause an increasing on traffic accidents, vehicle operating and maintenance costs. Additionally, they not only cause for traffic congestion problems and crashes, they but also cause slower movement speeds, longer journey times, longer queuing, higher traffic based noise and severe discomfort problems (Akgüngör, Demirel 2008;Ben-Edigbe 2010, 2016Dell' Acqua, Russo 2011;Aydın, Topal 2016). To determine and prevent deformation problems, many countries have been worked to monitor road surfaces steadily by using special devices and techniques (TRB 2004;TRRL 1991;Lee, Kim 2005;TRB 2010;Strazdins et al 2011;Žilionienė et al 2013;Aydın, Topal 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Deformations limit driving properties such as vehicle control, driving comfort and also cause an increasing on traffic accidents, vehicle operating and maintenance costs. Additionally, they not only cause for traffic congestion problems and crashes, they but also cause slower movement speeds, longer journey times, longer queuing, higher traffic based noise and severe discomfort problems (Akgüngör, Demirel 2008;Ben-Edigbe 2010, 2016Dell' Acqua, Russo 2011;Aydın, Topal 2016). To determine and prevent deformation problems, many countries have been worked to monitor road surfaces steadily by using special devices and techniques (TRB 2004;TRRL 1991;Lee, Kim 2005;TRB 2010;Strazdins et al 2011;Žilionienė et al 2013;Aydın, Topal 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The origins of environmental noise are in human activities and are especially associated with the process of urbanization and the development of transport (Kaklauskas et al 2009;Shukla et al 2009;Akgüngör, Demirel 2008;Daunoras et al 2008;Jović, Đorić 2010). One of the main sources of environmental noise in cities is related to road traffic.…”
Section: Introductionmentioning
confidence: 99%
“…TGV etc.) accompanied by a simultaneous demand of a high level of life comfort in the same place (obviously connected with keeping noise at an appropriately low level) (Bazaras 2006;Bazaras et al 2008;Akgüngör and Demirel 2008). The effects of noise include direct and cumulated negative influence on human health with a simultane- Various studies (Willich et al 2006) have confirmed the influence of noise on cardiac infarction risk in the places such as work and residence (Baltrėnas et al 2007a;Zavadskas et al 2007a, b).…”
Section: Introductionmentioning
confidence: 99%